Factors Affecting the Sudden Buying of Sportswear - Mohammadbagher Forghani Ozrudi; Ali Yaghobi (Shahid Bahonar University of Kerman, 2022)
The purpose of this study was to investigate the factors affecting the sudden buying of sportswear in sports stores in Mazandaran, Iran. This applied research has been done by descriptive-survey method. The statistical population of the study was the customers of a reputable sports store in Mazandaran province. 385 customers were selected through  available sampling method. A valid and reliable researcher-developed questionnaire was used for data collection, and structural equation modeling (SEM) was conducted for data analysis and hypotheses test. The results showed that the store environment (light, color, music, fragrance) has a positive effect on the sudden buying behavior of store customers. Moreover, the findings demonstrated that layout and physical appearance (Product availability, booth guide, product layout, building appearance, and staff coverage), as well as facilities available in the store and ancillary services (cafes and restaurants, amusement parks, child care centers), affect the psychological characteristics of customers' sudden buying behavior. By focusing on the research findings, the managers of sports stores can have a positive impact on customers' sudden buying and improving the selling approaches.